Electrocardiographic identification of the diastolic dysfunction in patients depending on hemodialysis - Annia Moraga Rodríguez; Alina Savigne Figueredo; Raúl Rizo Rodríguez; Alina Moraga Rodríguez; Alina Rodríguez Griñan (Centro Provincial de Información de Ciencias Médicas, 2016)
A descriptive and cross-sectional investigation of 64 patients (calculated size sample) with chronic kydney failure depending on hemodialytic treatment, assisted at the Hemodialysis Service of "Saturnino Lora Torres" Teaching Clinical Surgical Provincial Hospital in Santiago de Cuba, was carried out from May, 2013 to the same month in 2014, aimed at identifying the diastolic dysfunction in them through their electrocardiographic characteristics.  Among the main results there were the prevalence of male sex patients in the 40 to 59 age group and the pathological personal history of high blood pressure; besides, the electrocardiographic record showed that most of those affected presented a left ventricular growth pattern, with more incidence in those undergoing hemodialysis for more than a year.